Studies on the early development of mammalian embryos by nuclear transplantation - Smith, Lawrence C. (The University of Edinburgh, 1990)
The early development of mammalian embryos has been investigated using a technique of nuclear transplantation. Studies concentrated on the interactions between donor nuclei and recipient cytoplasm of reconstituted sheep and mouse embryos by analysing their ability to support cell division and to develop further in vitro or in vivo to the blastocyst stage. Sheep experiments showed that some nuclei derived from 16-cell blastomeres (day-4) and cells from the ICM of early blastocysts (day-6) can support development to term and retain similar potential to support development in vivo to the morula-blastocyst stage when fused to 'enucleated' secondary oocytes. The highly beneficial effect of adding cytochalasin B for one hour to the medium immediately after fusion indicated an effect of microfilament-dependent cytoskeletal mechanisms on transplanted nuclei at the time of activation.

Cell cycle stage effects were detected for recipient cytoplasm and donor nuclei of reconstituted 1-and 2-cell mouse embryos. Synchronous transplantations enabled higher proportions of embryos to develop in vitro to blastocysts when fusing embryonic fragments from the same cell cycle. However, transplantations using nuclei and cytoplasm from different cell cycles produced more blastocysts when the recipient cytoplasm came from later stages of the either 1st or 2nd cell cycle. Karyoplasts from later stages of the cell cycle were also more able to support development in transplantations to 1-and 2 -cell enucleated embryos.

Cleavage time was controlled by interactions between nucleus and cytoplasm already at the 1-cell stage with an indication that it may be necessary for DNA replication to be completed before mitosis and cytokinesis. Karyoplasts from transcriptionally inactive embryos were unable to support development when fused to cytoplasm after transcriptional activation suggesting a role for maternal cytoplasmic m e.ssages in activating transcriptionally inactive embryonic nuclei. Electrofusion parameters for strength and duration of the d .c . pulse were established for fusing mouse and sheep embryos. Preceding a .c. pulses were helpful in aligning 2-cell mouse embryos between the electrodes and improved fusion rates in sheep embryos when using ICM cells.

Together, these experiments have enabled a better understanding of the n u cleocytoplasmic control mechanisms during early stages of mammalian development. The results with sheep embryos revealed potential applications for the production of genetically identical farm animals and, assuming that embryonic stem cells can be isolated from farm animals and that these have similar potential as ICM cells, nuclear transplantation may become the most efficient means of producing non-chimaeric transgenic offspring from transformed embryonic stem cells.